Rhizosphere Microbial Population Growth, Nodulation and Yield in Camellia Sinensis under Different Climatic Conditions - Pathak, Dr R K (American Journal of Biology and Natural Sciences, 2025)
Tea (Camellia sinensis L.) is a globally significant commercial crop whose productivity is intricately linked to rhizosphere microbial communities. This study investigated the relationship between rhizosphere microbial populations, nodulation patterns, and tea yield under varying climatic conditions across three distinct agro-ecological zones. A comprehensive 24-month field study was conducted in tropical, subtropical, and temperate regions, examining bacterial, fungal, and actinomycetes populations alongside plant growth parameters. Results demonstrated that subtropical conditions (20-25°C, 1800-2200mm rainfall) supported optimal microbial diversity (8.7 × 10⁷ CFU/g soil for bacteria) and highest tea yield (2,450 kg/ha). Temperature and moisture significantly influenced microbial population dynamics (p<0.01), with bacterial populations showing 45% higher density in moderate moisture conditions compared to extreme wet or dry periods. Correlation analysis revealed strong positive relationships between total microbial count and fresh leaf yield (r=0.84, p<0.001). These findings provide crucial insights for sustainable tea cultivation practices under changing climate scenarios.